(untitled) (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyze the use of the Education Management Information System (EMIS) in managing student data at Madrasah Ibtidaiyah Nurul Yaqin Kuala Kurun. The study used a qualitative method with a case study approach. Data were collected through observation, interviews with EMIS operators, and documentation. Data analysis was conducted using the Miles and Huberman model which includes data reduction, data presentation, and conclusion drawing. The results showed that the implementation of EMIS at MI Nurul Yaqin Kuala Kurun has been running well, supported by teachers’ and staff’s understanding of EMIS functions, the availability of adequate devices and internet networks, and student data management integrated with Verval PD. In addition, data evaluation and updates are carried out periodically to ensure the accuracy and validity of student data. These findings indicate that the use of EMIS contributes to increasing the effectiveness and accuracy of student administrative data management at the madrasah